El Excentrico, 1974-01-05 - Garcia, Humberto:::Publisher::::::::::::; Garcia, Bert:::Manager::::::::::::; Garcia, Marc:::Editor:::::::::::: (Garcia Printing; San Jose, California, 2023)
January 5, 1974 [5 de enero de 1974]. No volume or issue number. Cover has photograph of Billy Ramos, recipient of the Man of the Year Award from the N. S.J. Optimist Club.